Cytokine fibroblast growth factor 10 (FGF10) polymorphisms are associated with risk of myopia in young children. Issue 9 (25th April 2019) - Sun, Wei; Li, Yinan; Li, Jing; Zhang, Xiaoming; Feng, Qingyang; Zhang, Zhenyu; Kang, Jianfang; Huang, Xuelin
Abstract: Myopia has become a major public health issue worldwide. Identification of genetic loci related to myopia in young children may advance our knowledge of the pathogenesis of myopia. Fibroblast growth factor 10 (FGF10) plays essential roles for the development of myopia through modulating extracellular matrix‐associated genes. Studies revealed that genetic variants of FGF10 were associated with extreme myopia in adults. However, their associations with susceptibility of myopia in young children, which are less affected by confounding factors and more suitable for studying genetic factors of myopia, have not been explored. In the current study, we evaluated 13 tagSNPs that captured 100% of genetic variation in the FGF10 gene region for their associations with myopia in a large Chinese case‐control study with 900 myopia children and 900 nonmyopia children. We found rs2973644 was significantly associated with increased risk of myopia (odds ratio [OR]: 1.26; 95% confidence intervals [CI]: 1.06‐1.49; P  = 0.009). furthermore, rs339501 (OR: 1.73; 95% CI: 1.18‐2.53; P  = 0.005), rs2973644 (OR: 1.57; 95% CI: 1.13‐2.19; P  = 0.007), and rs79002828 (OR: 1.83; 95% CI: 1.20‐2.77; P  = 0.005) were significantly associated with increased risk of high myopia in young children. Functional assessment of rs2973644 by luciferase assays revealed the risk G allele causes a higher expression level of FGF10 than the protective A allele. Our results do support that genetic variants of cytokine FGF10 are associated with susceptibility of myopia (as well as high myopia) in young children and further exploration are needed for myopia in children. Abstract : Our results do support that genetic variants of cytokine fibroblast growth factor 10 are associated with susceptibility of myopia (as well as high myopia) in young children and further exploration are needed for myopia in children.